An Overview of Nursing Education in Nepal - Shrestha, Pragya; Poudel, Kamala; Pokharel, Astha Sharma (Journal of Universal College of Medical Sciences, 2020)
Nursing is the most valued public service leaning profession. The quality of nursing education and future of nurse remains a growing concern with international standards in Nepal. The perspective of nursing educationists reveals the scholastic, academic and practical sight to understanding of advancement in the nursing education. Nepal has been running nursing education in the Government as well as in private sectors throughout the country. Nursing education focused with changes as center of attention at the certificate level to highlight prospective functions in the public health and at the bachelor level to focus on advancement of leadership skills. There are many problems in the existing nursing education which need to be addressed by the concerned authority for quality nursing education in the country. Nepal Nursing Council Act has made a mandatory provision that prior to granting approval to establish and operate a nursing educational institution; the concerned body shall consult the council for establishing and operating any nursing educational institution. The continuous and routine supervision and monitoring is needed to be made from the university as well as from the Nepal Nursing Council, Ministry of Education.